72 Acute kidney injury following percutaneous coronary intervention for acute coronary syndromes – incidence, aetiology, risk factors and outcomes. (4th June 2021) - Carande, Elliott; Brown, Karen; Jackson, David; Maskell, Nicholas; Kouzaris, Loukas; Greene, Giles; Mikhail, Ashraf; Obaid, Daniel
Abstract : Background: Acute kidney injury (AKI) is a recognised complication of percutaneous coronary intervention (PCI). We investigated the predictors, aetiology and long-term outcome of AKI following PCI for acute coronary syndromes (ACS). Methods: Two thousand nine-hundred and seventeen patients undergoing PCI for ACS were retrospectively investigated. AKI incidence was identified and cardiovascular and demographic risk factors, and dates of death were collected. Results: After exclusion, 198 patients (7.2% undergoing PCI) had an AKI: 14.1% of these AKI patients presented in cardiogenic shock, whilst 5.1% of patients had an elevated ESR and/or eosinophil count and were classified as atheroembolic renal disease (AERD). Statistically significant risk factors for developing AKI were increased age (OR 1.04, 95% Cl 1.03 to 1.06, p<0.0001), diabetes (OR 1.56, 95% Cl 1.09 to 2.21, p=0.0129), heart failure (OR 2.30, 95% Cl 1.22 to 4.15, p=0.0073), femoral access (OR 1.47, 95% Cl 1.02 to 2.10, p=0.0357) and cardiogenic shock on arrival (OR 2.92, 95% Cl 1.72 to 4.81, p<0.0001). Significant association with mortality at 1-year was found in patients with an AKI (OR 4.33, 95% Cl 2.89 to 6.43, p<0.0001), age (OR 1.08, 95% Cl 1.06 to 1.09, p<0.0001), heart failure (OR 1.92, 95% Cl 1.05 to 3.44, p=0.032), femoral access (OR 2.05, 95% Cl 1.41 to 2.95, p=0.0001), and cardiogenic shock (OR 3.63, 95% Cl 2.26 to 5.77, p<0.0001). Analysis of survival demonstrated a hazard ratio of mortality of 4.23 in the AKI group when compared to non-AKI patients (95% Cl 3.00 to 5.98, p<0.0001) (see figure 1 ). Significant associations with 1-year mortality in AKI patients were age (OR 1.04, 95% Cl 1.01 to 1.07, p=0.011), and cardiogenic shock (OR 4.40, 95% Cl 1.56 to 10.90, p=0.004). Patients with AERD AKI had a 1-year mortality rate of 40.0% and a 1-year renal replacement therapy requirement of 22.2%. This was compared to a 1-year mortality rate of 33.8% in AKI patients of any aetiology, and a renal replacement therapy requirement of 8.0%. Conclusion: AKI after urgent PCI is strongly associated with worse outcome. Risk factors for developing AKI were age, diabetes, heart failure, femoral access and cardiogenic shock. Risk of mortality at 1-year were the development of AKI, age, femoral access and cardiogenic shock. AERD occurred in 5.1% of those who develop an AKI and is an often-overlooked condition with poor outcome and likelihood of long-term renal replacement requirement. Early identification of patients is important to provide appropriate supportive care. Conflict of Interest: None